Using cone beam computed tomography to examine the prevalence of condylar bony changes in a Turkish subpopulation - NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2016)
Background/Purpose: The aim of this study was to characterize the condylar bone changes in the temporomandibular region using cone-beam computed tomography (CBCT) and to determine the prevalence of these changes in a population. Materials and Methods: CBCT images of the temporomandibular joints (TMJs) of 795 patients (426 females, 369 males) were retrieved from the computer database. The cross-sectional, coronal and sagittal views of 1-mm-thick sections of the TMJ were generated using CBCT. Age, gender, and bone changes on both condyles were recorded, and data were analyzed using a Chi-square test and McNemar's test to evaluate comparisons between qualitative data (IBM Corp., Armonk, NY). Results: No bone changes were observed in 78.4% (n = 623) of the TMJ samples obtained from the right side. Osteoarthritic changes were observed in 17.9% (n = 142) and developmental changes in 2.6% (n = 21) of the cases. On the left side, osteoarthritic changes were observed in 11.6% (n = 142) of the cases while developmental changes were observed in 2.6% (n = 21). Moreover, 82.4% (n = 655) of the TMJ samples showed no changes. When the age groups were compared in samples obtained from both right and left TMJs, the prevalence of bone changes increased by the age of 60 years and older. Conclusion: The prevalence of degenerative condylar bone changes increased with increasing age and was more frequent in women and right condyle.
Keywords: Bone changes; cone beam computed tomography; temporomandibular joint; TEMPOROMANDIBULAR-JOINT; RADIOGRAPHIC FINDINGS; MORPHOLOGICAL-CHANGES; MANDIBULAR CONDYLE; PAIN; AGE; CT; OSTEOARTHROSIS; DIAGNOSIS; POSITION